How Powerful is Your Customers’ Reaction to Carbon Performance? Linking Carbon and Firm Financial Performance - Rokhmawati, Andewi; Gunardi, Ardi; Rossi, Matteo (International Journal of Energy Economics and Policy, 2017)
This study aims to examine the effect of greenhouse gas (GHG) emissions on Return on Sales (ROS) that is moderated by customers’ response to firm activities to reduce GHG emissions. The Moderating Regression Analysis with cross-sectional data was utilized to examine the effects. The sample comprised 102 listed manufacturing firms listed in the Indonesian Capital Market in 2011. Sampling was based on the availability of firms’ financial reports in 2011, annual reports in 2014 and the availability of data of firm about the types and amounts of fossil fuels, as well as the amount of electricity, consumed by the firms in 2011. Surprisingly, the results showed that CO2e intensity has a positive significant effect on ROS. Customers’ response to the firm effort to reduce GHG emission has a positive and significant effect on ROS. Finally, Customers’ responses strengthen the effect of CO2e intensity on ROS. The finding of the positive significant effect of CO2e intensity on firm financial performance contrasts with the findings of previous studies carried out in several developed countries. The finding of the research is that the mediating variable of customers’ responses strengthens the effect of CO2e intensity on ROS. The positive significant effect found in this study has been explained with reference to Indonesia’s particular circumstances as a developing country. Keywords: GHG Emissions, Return on Sales, Instrumental Stakeholder Theory, Indonesian Listed Manufacturing Firms. JEL Classifcations: G3, L6, M1, Q5